EVALUATION OF NUTRIENTS INTAKE AND ABDOMINAL CIRCUNFERENCE IN PATIENTS WITH METABOLIC SYNDROME IN THE REGION OF VALE DOS SINOS, RS (Fiep Bulletin - online, 2014)
Metabolic syndrome (MS) is a cardiovascular risk factor. Proper eating habits, associated to other alterations on life style has contributed to a better control of the disease, preventing its complications and increasing quality of life. The aim of this study is to assess nutrients intake and abdominal circunference in patients with metabolic syndrome in the region of vale dos Sinos, RS. In this descriptive study, 50 patients n=13 male (M) and n=37 female (F), aged between 30 and 60 years, randomly selected, undertook 24- hour food record and alimentary enquiry in order to have their eating habit and nutrient intake identified. Figures were caculated through the Brazilian food composition table (TACO) and the program Diet Win Professional. Abdominal circunference (CA) was measured through tape measure placed at the longest extension between iliac crest and the back. Data was analysed statistically through ANOVA and Pearson Correlation. Regardin to intake, results showed protein over recommendation (19.4% = p
Keywords: Metabolic Syndrome; nutrients; insulin resistance; circumference abdominal.